MULTICULTURAL VALUES IN INDONESIAN PRIMARY SCHOOLS - Mansur Akil (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2010)
The research aimed to understand ways of implementing multicultural values in Indonesia primary schools. This case study attempted to discover the multicultura values in primary school curriculum documents and teacher's perspective on how to promote the multicultural values in primary shcool students, by interviewing primary school teacher in Makassar and examining primary school curriculum documents. The investigation showed that teaching the values of tolerance, respecting diversity, acknowledging similarities and maintaining native languages and local identy should be done gradually by initially introducing the symbols of multicultural values through picture, videos, and observations, then teaching children through modeling and attitudes of inclusiveness. More importantly is teachers' knowledge on multiculturalism so that they could behave equally towards students and colleagues in school setting. Finally, multiculturalism should be embedded in the schools through celebration of cultures, ethnics and language diversity, through cultural festivals, food exhibition, local art and dance shows, music contests, drama, and literature. Keywords: Multicultura Values, Implementing, Primary School, Teacher Views.